Efficacy of Application of Plasma Rich in Growth Factors Along with the Tunnel Technique for Treatment of Gingival Recession: a Clinical Trial - Fatemeh Ahrari; Farshad Keshavarzi; Ali Bijani; Niloofar Jenabian (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: The tunnel technique has shown promising results in treatment of gingival recession. Plasma rich in growth factors (PRGF) is considered effective for soft tissue regeneration since it is a rich source of growth factors. Purpose: This clinical trial aimed to assess the efficacy of PRGF along with the tunnel technique and connective tissue graft for treatment of gingival recession. Materials and Method: In this controlled clinical trial, 20 areas around anterior and posterior teeth in 3 patients with gingival recession were bilaterally selected. The tunnel technique was used with and without PRGF in the test and control groups, respectively (10 areas in each group). The keratinized gingival width (KGW), clinical attachment level (CAL), clinical probing depth (PD), cementoenamel junction (CEJ) to mucogingival junction (MGJ) distance, and the esthetic visual analog scale (EVAS) score were evaluated preoperatively and at 6 weeks and 3 months, postoperatively. The gingival recession width (RW) and vertical recession depth (VRD) were assessed preoperatively and at 2 weeks and 3 months, postoperatively. The pain visual analog scale (PVAS) score was measured at 1, 3 and 7 days, post-treatment and the healing index (HI) was measured at 1, 3 and 7 days and 1 month, postoperatively. The root coverage percentage was assessed during 3 months. Paired t-test and repeated measures ANOVA were used for statistical analyses. p Value< 0.05 was considered statistically significant. Results: Significant improvements were noted in all tested parameters in both groups (p< 0.05). The mean root coverage percentage after 6 months was 88.68%±20.69% and 78.77%±24.94% in the test and control groups, respectively. None of the tested parameters were significantly different between two groups (p> 0.05). Conclusion: Treatment of gingival recession with the tunnel technique can yield favorable clinical outcome, irrespective of the employment of PRGF.